Geological History of the Stingless Bees (Apidae: Meliponini) - Engel, Michael S.; Michener, Charles D. (My University, 2013)
A brief overview of the fossil record of stingless bees is provided. The eleven fossil species of Meliponini are discussed in order of descending geological age and placed within the paleoecological and paleogeographical context of their period. The earliest fossil meliponine is Cretotrigona prisca from the Late Cretaceous of New Jersey, USA, while the youngest are various species preserved in relatively modern copals. The implications of these species for understanding the evolutionary history of Meliponini are briefly discussed.
Keywords: Anthophila; Apoidea; Biogeography; Climate change; Meliponini; Paleontology; Departamento de Análisis y Control; Facultad de Farmacia y Bioanálisis; Medicina y Salud; Monografías